El sacrificio de la mujer viuda en el mundo indoeuropeo - Marcos Casquero, Manuel-Antonio (Gerión. Revista de Historia Antigua, 2001)
The widow in the Roman World: Religious restriction affecting the re-married woman (bis nuptae). In the indoeuropean prehistory, widows were required to follow the same fate than their husbands, right after the husbands’ death. This paper analyzes this practice in different cultures of indoeuropean background, with special attention to the Greek mythological stories, and the sati or suttee ceremonies among the Hindues. The ideologies on whinch this practices are based will be reviewed.